2008 Florida Land Value Survey: Farmland Prices Down - Rodney L. Clouser; Ronald Muraro; Laila Racevskis; Charles Moss; Allen Morris (EDIS)
FE798, a 6-page report by Rodney L. Clouser, Ronald Muraro, Laila Racevskis, Charles Moss, and Allen Morris, presents the results of a 2008 land value survey to estimate the value of different types of agricultural land for geographic regions of the state. Includes references. Published by the UF Department of Food and Resource Economics, April 2009.